PENGARUH EKSPLAN DAN ZPT TERHADAP PERTUMBUHAN nEPEnTHES ALBOmARGInATA SECARA In VITRO - Sukamto, Lazarus Agus (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Nepenthes albomarginata Lobb ex Lindl. is a carnivorous plant, distributes in severalÃ‚Â regions in Indonesia. The plant population decreases drastically because of overÃ‚Â exploitation and ruining nature habitat. Plant propagation by nature and cutting are notÃ‚Â enough to rehabilitation its population. In vitro culture of N. albomarginata was carriedÃ‚Â out using plantlets grown from the seeds in vitro. Plantlets were cut to became two partÃ‚Â explants, consisted of shoot tip and under-shoot tip cuttings. These cutting explants wereÃ‚Â grown on Murashige & Skoog (MS) media with addition of plant growth regulators ofÃ‚Â 6-benzylaminopurine (BA), combined with or without-naphthalene acetic acid (NAA) orÃ‚Â 2,4-dichlorophenoxyacetic acid (2,4-D) at 1 mg/l. Shoot tip cuttings of N. albomarginataÃ‚Â formed double multiple shoot 25,00% on control; formed triple multiple shoots 25,00% onBA 1 mg/l treatment; formed callus 37,50%, triple or quartet shoots 25,00% and rootedÃ‚Â plantlets 25,00% on BA 1 mg/l + NAA 1 mg/l treatment. The under-shoot tip cuttings ofN. albomarginata formed double Ã¢â‚¬â€œ triple shoots 25,00% and rooted plantlets 37,50% onÃ‚Â control; formed double Ã¢â‚¬â€œ triple shoots 25,00% and rooted plantlets 12,50% on BA 1 mg/ltreatment; formed callus 12,50%, double - pentacle shoots 37,50% and rooted plantletsÃ‚Â 25,00% on BA 1 mg/l + NAA 1 mg/l treatment. 2,4-D 1 mg/l or its combined with BA 1mg/l treatment caused deadly shoot tip or under-shoot tip explants. The combinationÃ‚Â of BA 1 mg/l + NAA 1 mg/l was the best treatment for producing callus, multiple shootsand rooted plantlets of N. albomarginata.